Ultra peripheral heavy ion collisions and the energy dependence of the nuclear radius - Roldao, C. G.; Natale, A. A. (Elsevier B.V., 2004)
To estimate realistic cross sections in ultra peripheral heavy ion collisions we must remove effects of strong absorption. One method to eliminate these effects make use of a Glauber model calculation, where the nucleon-nucleon energy dependent cross sections at small impact parameter are suppressed. In another method we impose a geometrical cut on the minimal impact parameter of the nuclear collision ((b)min > R-1 + R-2, where R-i is the radius of ion 'i'). In this last case the effect of a possible nuclear radius dependence with the energy has not been considered in detail up to now. Here we introduce this effect showing that for final states with small invariant mass the effect is negligible. However when the final state has a relatively large invariant mass, e.g., an intermediate mass Higgs boson, the cross section can decrease up to 50%. (C) 2003 Published by Elsevier B.V.